PENDAPATAN USAHA PEMBUATAN INSTAN TEMU PUTIH DI KAWASAN LERAGERE KECAMATAN LEBATUKAN KABUPATEN LEMBATA - Asnah Asnah; Bediona Felik (BUANA SAINS, 2008)
White temu is one of plants which is included in pharmaceutical commodities and has potentially prospect to be developed in Leragere. So far, white temu has not been managed intensively because there is lack of knowledge about the importance of white temu to explore to be pharmaceutical product. In fact, white temu will give an opportunity to increase people income, especially if white temu is formed as instant drink white temu. This research is aimed to study cost, revenue, profit and efficiency of white temu producing in Leragere area. Location is purposively determined as Leragere is considered as white temu area development. The samples are decided as many as 25 people, in line with quota systematic sampling with reason of population homogeneously characteristic. Collected data is included primary and secondary data, which is managed by using farming analysis tool in line with research goal and it is interpreted as equal as analysis result